Sport ethics : - Lumpkin, Angela (McGraw-Hill, 2003)
This text challenges students to examine how to respond to moral issues and dilemmas in sport. The book includes philosophic theory that has proven effective in the moral development of athletes. The theory is balanced with applications and thought-provoking questions. Each chapter provides a historical and sociological perspective on the issues facing youth, interscholastic, intercollegiate, Olympic, and professional sport.